Isolation and high-performance liquid chromatography analysis of chettaphanin I in extracts from Cladogynos orientalis roots - Kongkiatpaiboon, Sumet; Rojsanga, Piyanuch; Sithisarn, Pongtip (Agriculture and Natural Resources, 2022)
Importance of the work: Cladogynos orientalis Zipp. ex Span. is a Thai traditional plant that has been used for antiflatulence and anti-stomach pain effects. Objectives: To isolate and quantitative analysis of chettaphanin I in C. orientalis root extracts and fractions. Materials & Methods: Chettaphanin I was isolated from the root extract of C. orientalis using chromatographic techniques and structurally identified using spectroscopic and spectrometric techniques. A high-performance liquid chromatography (HPLC) method was developed and validated for the quantitative analysis of chettaphanin I in the root extracts and fractions from this plant. Results: It was found that the root ethanol extract contained a higher amount of chettaphanin I than the root decoction extract (2.97 ± 0.14% weight per weight (w/w) and 1.82 ± 0.12% w/w, respectively, in the dried extract). Using a solvent-solvent extraction process from the root decoction extract, the obtained aqueous fraction contained a significant amount of chettaphanin I (6.19 ± 0.36% w/w of dried extract) while the dichoromethane fraction contained a very low amount. Main finding: Chettaphanin I was a compound mainly found in the roots of C. orientalis which could be used as a marker for the quality control of raw materials and root extracts of this plant. HPLC method was developed and validated for quantitative analysis of chettaphanin I.